ON THE EXAMPLE OF STUDENTS OF THE DIRECTION OF CHEMICAL TECHNOLOGY OF THE DEVELOPMENT OF CHEMICAL TECHNOLOGICAL COMPETENCIES - Jo‘rayeva Barno Abdikhalilovna; Nabiev Abdurakhim Abdukhamidovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2024)
In this article, the theoretical importance of using interactive media and interactive educational technology as a method for improving chemistry and its teaching methodology in higher education is explained. Also, modern advanced pedagogical technologies encourage future chemistry students to independently study and analyze acquired knowledge and skills by using interactive media. The use of interactive media and interactive educational technologies as a method in improving chemistry and its teaching methods in higher education not only broadens students’ worldview, but also encourages independent thinking, creative research, and increases their initiative